Police Integrity Lost: A Study of Law Enforcement Officers Arrested - Brewer, Steven L (2016)
There are no comprehensive statistics available on problems with police integrity, and no government entity collects data on all criminal arrests of law enforcement officers in the United States. Police crimes are those crimes committed by sworn law enforcement officers with the general powers of arrest. These crimes can occur while the officer is either on- or off-duty and include offenses committed by officers employed by state and local law enforcement agencies. This study provides a wealth of data on a phenomena that relates directly to police integrity— data that previously did not exist in any usable format. The first goal of the study is to determine the nature and extent of police crime in the United States. The objective for this goal is to determine the incidence and prevalence of officers arrested. A second goal is to determine what factors influence how an agency responds to arrests of its officers. Objectives for this goal are to determine whether certain factors influence agency response and employment outcomes: (a) severity of crimes for which officers are arrested; (b) level of urbanization for each employing agency; (c) geographic location for each employing agency; (d) length of service and age of arrested officers; and, (e) criminal case outcomes. A final goal is to foster police integrity by exploring whether officer arrests correlate with other forms of police misconduct. Objectives for this goal are to determine whether arrested officers were also named as a civil defendant in any 42 U.S.C. §1983 federal court actions during their careers, and to inform practitioners and policymakers of strategies that will better identify problem officers and those at risk for engaging in police crime and its correlates. The advent of nationwide, objective, and verifiable data on the law-breaking behavior of sworn officers and provides potential benefits to law enforcement agencies that connect the technical expertise of researchers to criminal justice policymakers and practitioners. These data 2 provide direct guidance in three areas. First, the study provides agencies information on the types of crime that are most frequently perpetrated by police officers. Second, the research provides information on the relationship between police crimes and other types of misbehavior that collectively comprise the problem officer. Third, nationwide data on police crimes and the manner in which arrested officers are organizationally sanctioned provides points of comparison for law enforcement agencies that confront these problems, as well as information on the degree to which law enforcement agencies tend to sanction or ignore certain crimes committed by officers. This is a quantitative content analysis study of archived records reporting several thousand arrests of police officers during the years 2005-2011. The primary information source is the Google News search engine and its Google Alerts email update service. Chi-Square was used to measure the statistical significance of the association between two variables measured at the nominal level. Cramer’s V was utilized to measure the strength of the Chi-Square association. Stepwise binary logistic regression was used to determine which of the predictor variables are statistically significant in multivariate models. Classification tree analysis was utilized to uncover the causal pathways between independent predictors and outcome variables. The Google News searches resulted in the identification of 6,724 cases in which sworn law enforcement officers were arrested during the years 2005 through 2011. The cases involved the arrests of 5,545 individual sworn officers employed by 2,529 nonfederal state and local law enforcement agencies located in 1,205 counties and independent cities in all 50 states and the District of Columbia. The findings indicate that nonfederal law enforcement officers were arrested nationwide during 2005-2011 at a rate of 0.72 officers arrested per 1,000 officers, and at a rate of 1.7 officers arrested per 100,000 population nationwide